India. Administrative Justice : some necessary reforms (Oxford)
In 1978 a Committee was formed under the auspices of JUSTICE (The British Sec tion of the International Commission of Jurists) and All Souls College, Oxford, to undertake a full scale examination of administrative law in the United Kingdom. The background to this was a series of seminars held in All Souls College by the English Law Commission (1966 and 1968), following which the Commission recommended the setting up of a Royal Commission to examine defects in the administrative law of the UK. Successive governments refused to take action and thus the present unofficial committee was formed. This book contains the results of the Committee's work, which include: urging the adoption of a clear and authoritative statement of administrative law principles, the adoption of codes of practice by government agencies, exam ination of the role of the Ombudsman, some suggestions about remedies, and the function of official inquiries.
Keywords: Administative law Great Britain